Titin fragment is a sensitive biomarker in Duchenne muscular dystrophy model mice carrying full-length human dystrophin gene on human artificial chromosome - Yosuke Hiramuki; Miwa Hosokawa; Kayo Osawa; Taku Shirakawa; Yasuhiro Watanabe; Ritsuko Hanajima; Hiroyuki Kugoh; Hiroyuki Awano; Masafumi Matsuo; Yasuhiro Kazuki (Scientific Reports)
Abstract Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder caused by mutations of the dystrophin gene, which spans 2.4 Mb on the X chromosome. Creatine kinase (CK) activity in blood and titin fragment levels in urine have been identified as biomarkers in DMD to monitor disease progression and evaluate therapeutic intervention. However, the difference in the sensitivity of these biomarkers in DMD remains unclear. Previously, we generated transchromosomic mice carrying the full-length human dystrophin gene on a human artificial chromosome (DYS-HAC1) vector. The human dystrophin derived from DYS-HAC1 improved pathological phenotypes observed in DMD-null mice, which lack the entire 2.4 Mb of the dystrophin gene. In this study, we compared the values of plasma CK activity and urine/plasma titin fragment levels in wild-type (WT), DYS-HAC1, DMD-null, and DYS-HAC1; DMD-null mice. Plasma CK activity and urine/plasma titin fragment levels in DMD-null mice were significantly higher than those in WT mice. Although plasma CK activity showed no significant difference between WT and DYS-HAC1; DMD-null mice, urine/plasma titin fragment levels in DYS-HAC1; DMD-null mice were higher than those in WT mice. Human dystrophin in DYS-HAC1; DMD-null mice drastically improved muscular dystrophy phenotypes seen in DMD-null mice; however, the proportion of myofibers with central nuclei in DYS-HAC1; DMD-null mice had a tendency to be slightly higher than that in WT mice. These results suggest that urine/plasma titin fragment levels could be a more sensitive biomarker than plasma CK activity.